ANALISIS KESULITAN GURU DALAM MENGEMBANGKAN DESAIN PEMBELAJARAN TEMATIK KELAS IV SD N JARAKAN BANTUL TAHUN AJARAN 2017/2018 - Saputra, Fauzan Irsandi; Wardani, Kristi (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2019)
The purposes of this study is to describe (1) the analysis of teacher's difficulties in developing and designing the fourth grade thematic design of SD N Jarakan Bantul Yogyakarta in academic year 2017/2018 and (2) the solution to overcome the difficulties faced by teachers in throwing thematic learning of fourth grade students SD N Jarakan Bantul Yogyakarta in academic year 2017/2018. This research is a qualitative research. This research is a qualitative research that is conducted in SD N Jarakan Bantul Yogyakarta. The subject of the research are principal, teachers, and students. Data collection technique use interview, observation, and documentation. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. The results of the study showed that (1) the teacher's difficulties in developing the fourth grade thematic design of SD N Jarakan Bantul Yogyakarta to determine the time allocation, assessment, learning of students, developing lesson plan. When designing the learning process the teacher also faces difficulties because while the teacher's learning still beheads one of the subjects. Teachers also have difficulties when made the syllabus. (2) The solution that can be used to face the difficulties of the teacher is by conducting regular meetings through KKG activities, conducting the training, and learning activities are not glued by teacher book, but in learning teacher should pay attention to basic competence and the implementation requirements of thematic learning.